Effects of transcranial alternating current stimulation to the supplementary motor area on motor learning - Yamamoto, Shunpei; Miyaguchi, Shota; Ogawa, Takuma; Inukai, Yasuto; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Behavioral Neuroscience, 2024)
Transcranial alternating current stimulation (tACS) is a noninvasive method for brain stimulation that artificially modulates oscillatory brain activity in the cortical region directly beneath the electrodes by applying a weak alternating current. Beta (β) oscillatory activity in the supplementary motor area (SMA) is involved in motor planning and maintenance, whereas gamma (γ) oscillatory activity is involved in the updating of motor plans. However, the effect of applying tACS to the SMA on motor learning has not yet been investigated. This study assessed the effects of applying tACS to the SMA on motor learning. Forty-two right-handed healthy adults (age 20.6 ± 0.5 years, 24 men and 18 women) were included. Motor learning was assessed using a visuomotor tracking task with pinch tension of the right thumb and right forefinger. Each trial lasted 60 s, and the error rates were measured. Conductive rubber electrodes were attached to the SMA and the left shoulder for tACS. Stimulation was applied at an intensity of 1.0 mA and frequencies of 70 and 20 Hz in the γ-tACS and β-tACS treatment groups, respectively. The sham group was only administered a fade-in/out. The visuomotor tracking task was performed for 10 trials before tACS and 10 trials after tACS. Two trials were conducted on the following day to determine motor skill retention. The average deviation measured during 60 s was considered the error value. Pre-stimulation learning rate was calculated as the change in error rate. Post-stimulation learning rate and retention rate were calculated as the change in error rate after stimulation and on the day after stimulation, respectively. In both the stimulation groups, differences in pre-stimulation learning, post-stimulation learning, and retention rates were not significant. However, in the γ-tACS group, baseline performance and pre-stimulation learning rate were positively correlated with post-stimulation learning rate. Therefore, applying γ-tACS to the SMA can increase post-stimulation learning rate in participants exhibiting low baseline performance and high pre-stimulation learning rate. Our findings suggest that motor learning can be effectively enhanced by applying γ-tACS to the SMA based on an individual's motor and learning abilities.